Pengaruh Return on Asset dan Related Party Transaction terhadap Fraudulent Financial Statement pada Perusahaan Konstruksi di Negara ASEAN - Dina Maryana; Reni Oktavia (Akuntansi, 2023)
This study aims to determine the effect of return on assets and related party transactions on fraudulent financial statements in construction sector companies listed on Stock Exchanges in ASEAN countries. The method in this study uses quantitative methods and data collection techniques, namely document analysis. The population in this study is a construction sector company listed on the Stock Exchange in ASEAN countries. Based on the research criteria, a sample of 120 companies was obtained. The data analysis technique used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, coefficient of determination, F test and t test. The results of the study show that return on assets has a positive effect on fraudulent financial statements. On the other hand, change in auditors and related party transactions have no effect on fraudulent financial statements. The coefficient of determination of 0.028 indicates the ability of ROA and RPT to explain changes in fraudulent financial statements of 2.8 percent, while the remaining 97.2 percent is explained by other factors.